A PROSPECTIVE OBSERVATIONAL STUDY OF DRUG PATTERN ON SKIN DISEASES AT A TERTIARY CARE HOSPITAL (World Journal of Current Medical and Pharmaceutical Research, 2019)
Background: Skin diseases have a serious impact on an individual’s health related quality of life. Occasionally skin diseases can be a manifestation of systemic diseases. Prescribing pattern studies are pre requisite for the formulation of drug policies. They offer useful methods for teaching and training in drug therapy and also identify the problems that arise from drug usage in healthcare delivery system and highlight the current approaches to the rational use of medicines. Aim: The aim of this prospective study is to assess the drug pattern of skin diseases in tertiary Care hospitals and their impact on patient’s health related quality of life. The objectives for this study were to perform an evaluate the prescribing pattern of skin diseases & assess the effect of skin conditions on patients quality of life. Methodology: A Prospective observational study was conducted in 190 adult patients presenting to the Department of Dermatology at various Tertiary Care Hospitals, Guntur, Andhra Pradesh, India for a period of 6 Months. Prescriptions of 190 patients attending dermatology outpatient department were collected and analysed. The variables assessed from the prescriptions includes the demographic profile of the patient, age, gender, socio - economic status, various common conditions related to skin, various classes of drug prescribed with their dosage form, dose, frequency and duration of administration. Results: In this study, a total of 190 populations were analysed among them majority of population accounting 53% of males and 47% of females. And the predominant age group of the presenting population was 21-30 years accounting 24%. The most common skin diseases are Tinea corporis (32.1%), Scabies (15.2%), Acne Vulgaris (8.9%), Urtricaria, and Eczema. Mostly patients were prescribed with antihistamines, corticosteroids and antifungal medications. Conclusion: From this study, we conclude that male population of age between 21-30 years are more prone to skin diseases. Fungal infections formed the majority of presenting disease conditions and the effect on patient’s Quality of life was small to moderate and large effect on patient’s quality of life was considerably negligible. The most common disease among study population is Tinea corporis. The most common drugs & dosage form prescribed in our study were anti-histamines& corticosteroids used as a topical ointments.